2018
DOI: 10.1016/j.icarus.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics of submicrometer-sized craters on regolith particles from asteroid Itokawa

Abstract: a b s t r a c tWe investigated impact crater structures on regolith particles from asteroid Itokawa using scanning electron microscopy. We observed the surfaces of 51 Itokawa particles, ranging from 15 μm to 240 μm in size. Craters with average diameters ranging from 10 nm to 2.8 μm were identified on 13 Itokawa particles larger than 80 μm. We examined the abundance, spatial distribution, and morphology of approximately 900 craters on six Itokawa particles. Craters with sizes in excess of 200 nm are widely dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
(73 reference statements)
1
9
0
3
Order By: Relevance
“…This corresponds to~1 × 10 −18 nm/yr, which is an extremely low rate. Submicron-sized impact craters on troilite in Itokawa particles show no evidence for whisker growth 51 . Moreover, examined troilite surfaces with iron whiskers do not correspond to crater floors.…”
Section: Discussionmentioning
confidence: 91%
“…This corresponds to~1 × 10 −18 nm/yr, which is an extremely low rate. Submicron-sized impact craters on troilite in Itokawa particles show no evidence for whisker growth 51 . Moreover, examined troilite surfaces with iron whiskers do not correspond to crater floors.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to the most studied lunar soils, the samples from Itokawa are highly immature, with some grains showing almost no signs of surface modification at the nanoscale (Noguchi et al 2014a(Noguchi et al , 2014b. While microscale craters and melt splashes associated with micrometeoroid impacts have been observed on a number of grains (Harries et al 2016;Matsumoto et al 2018), most of the rim features seen on Itokawa particles are linked to solar wind irradiation and sputtering (Keller and Berger 2014;Noguchi et al 2014b; Thompson et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…2016; Matsumoto et al. 2018), most of the rim features seen on Itokawa particles are linked to solar wind irradiation and sputtering (Keller and Berger 2014; Noguchi et al. 2014b; Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…• Based on the concentration of the Neon ion and the number density of the solar flare tracks of Itokawa particles, it was estimated that the particle size remained within few centimeters for a duration of 150-550 yr (Nagao et al 2011) and approximately thousands to tens of thousands of years (Noguchi et al 2014;Keller & Berger 2014), respectively. • Matsumoto et al (2018) demonstrated that the dominant cratering process on the Itokawa particles in the submicrometer range was caused by the secondary ejecta created by primary impacts on the Itokawa surface. If it is assumed that the secondary crater formation rate is equivalent to the lunar impact flux, the measured age based on the number of submicrometer craters can be estimated to be approximately thousands of years.…”
Section: Introductionmentioning
confidence: 99%